Analysis of Transformational Leadership Style and Organizational Culture and Its Influence on Employee Performance Through Work Motivation as an Intervening Variable - Norawati, Suarni; Alputra, Rahmat; Basem, Zamhir (DINASTI RESEARCH, 2025)
Every company's leader always expects maximum employee performance, therefore it is necessary to know what factors influence employee performance. This research was conducted at PT RIM Syam Gold Bangkinang, with the aim of the research to determine and analyze 1) the influence of transformational leadership style on employee performance; 2) the influence of organizational culture on employee performance; 3) the influence of work motivation on employee performance; 4) the direct influence of transformational leadership style on employee performance; 5) the direct influence of organizational culture on employee performance; 6) the indirect influence of transformational leadership style on employee performance through work motivation; 7) the indirect influence of organizational culture on employee performance through work motivation. This study uses primary data and secondary data, obtained using questionnaires, observations, interviews and research files. The population of this study was all employees of PT RIM Syam Gold Bangkinang, totaling 43 employees and all of them were used as samples, sampling was carried out using the census method. Data analysis and hypothesis testing were carried out using the SEM model and data processing was carried out using the SmartPLS version 3.00 program. The results of this study conclude that: 1) transformational leadership style has been proven to have a significant effect on employee performance; 2) organizational culture has been proven to have a significant effect on employee performance; 3) work motivation has been proven to have a significant effect on employee performance; 4) transformational leadership style has not been proven to have a direct effect on employee performance; 5) organizational culture has been proven to have a direct and significant effect on employee performance; 6) there has been proven to be an indirect effect of transformational leadership style on employee performance through work motivation; 7) there has been proven to be a significant indirect effect of organizational culture on employee performance through work motivation.